Electric field sensor data for AUV dive ABYSS 0232 during METEOR cruise M127 - Sven Petersen; Marcel Rothenbeck (PANGAEA, 2021)
A total of fifteen missions of the autonomous underwater vehicle (AUV) Abyss was performed in June 2016 over the TAG hydrothermal field as part of the EU-funded project Blue Mining. Each dive lasted a few hours.The processed electric anomaly data in longitudinal direction (along the flight path) and transverse direction (perpendicular to the flight direction) is provided here. More sensor data and the vehicles performance under water and core functions (roll, pitch, heading, power use, and many others) are recorded in the STATE file, see raw sensor data.